Problems of Legislation Systematization in the Sphere of Entrepreneurial Activity - ASSETOVA, Gulnur; KUBEYEV, Yerkin; KIZDARBEKOVA, Antonina (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018, 2019)
The paper looks at the process of systematization of Kazakhstan’s legislation in the sphere of entrepreneurial activity and problems associated with that. Based on comparison with specific regulations of the CIS member countries that observe codified laws in the field of entrepreneurship, the paper focuses on the necessity to accurately forecast the effect exerted by systematization of legislation and choosing its optimal form. The authors ascertain the fact that there is no doctrinal justification for performing systematization works, which results in the unreasonable use of particular public relations while enforcing legal regulation. In this regard, the article proposes to design a doctrine of systematization of the national legislation in the sphere of entrepreneurship. This will exclude redundant elements in the legal regulation system, thereby ensuring its normal functioning.